2016
DOI: 10.1016/j.neuroscience.2016.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptor mediated the propofol self-administration by dopamine D1 receptor in nucleus accumbens

Abstract: Propofol, a widely used anesthetic, can cause addictive behaviors in both human and experimental animals. In the present study, we examined the involvement of glucocorticoid receptor (GR) signaling in the molecular process by which propofol may cause addiction. The propofol self-administration model was established by a fixed ratio 1 (FR1) schedule of reinforced dosing over successive 14days in rats. On day 15, the rats were treated with dexamethasone, a GR agonist (10-100μg/kg), or RU486, a GR antagonist (10-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 29 publications
1
19
1
Order By: Relevance
“…Indeed, it was reported that D1 MSNs are important in the maintenance of propofol self-administration (Lian et al, 2013 ). Moreover, the systemic administration of a glucocorticoid receptor agonist in the nAc can regulate propofol self-administration behavior, altering the D1 receptor and c-Fos expression in rats (Wu et al, 2016 , 2018 ). Also, propofol increases DeltaFosB in nAc mediated by D1 receptors (Xiong et al, 2011 ) thus linking the rewarding effect of propofol directly to D1 MSNs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was reported that D1 MSNs are important in the maintenance of propofol self-administration (Lian et al, 2013 ). Moreover, the systemic administration of a glucocorticoid receptor agonist in the nAc can regulate propofol self-administration behavior, altering the D1 receptor and c-Fos expression in rats (Wu et al, 2016 , 2018 ). Also, propofol increases DeltaFosB in nAc mediated by D1 receptors (Xiong et al, 2011 ) thus linking the rewarding effect of propofol directly to D1 MSNs.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the fast onset of creating a short ecstatic and euphoric feeling, the capacity to induce sexual delusions, fantasies, and disinhibition, without many of the side effects that are associated with other drugs, and the fact of not being a controlled substance are the main reasons for its widespread abuse [ 158 , 160 ]. Pharmacodynamically, propofol increases dopamine concentrations in the nucleus accumbens , a phenomenon noted with other addictive psychoactive substances [ 161 164 ]. Chronic propofol abuse can result in tolerance, and repeated injections exceeding 100 times per day have been reported [ 163 , 165 ].…”
Section: Propofol Abusementioning
confidence: 99%
“…Cell experiments further confirmed the positivity of DEX in reducing the invasion and migration of cancer cells in rats with ovarian cancer. One previous study confirmed that mifepristone and propofol have certain effects in anti-tumor therapy [30]. IN addition, Check et al found that propofol drugs could affect the biological behavior of breast cancer cells, and the right amount of propofol could reduce the invasion and migration of cancer cells [31].…”
Section: Discussionmentioning
confidence: 94%